2017
DOI: 10.1148/radiol.2017161218
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Women with the BRCA1 or BRCA2 Mutation by Using Biannual Automated Breast US, MR Imaging, and Mammography

Abstract: Purpose To evaluate a multimodal surveillance regimen including yearly full-field digital (FFD) mammography, dynamic contrast agent-enhanced (DCE) magnetic resonance (MR) imaging, and biannual automated breast (AB) ultrasonography (US) in women with BRCA1 and BRCA2 mutations. Materials and Methods This prospective multicenter trial enrolled 296 carriers of the BRCA mutation (153 BRCA1 and 128 BRCA2 carriers, and 15 women with first-degree untested relatives) between September 2010 and November 2012, with follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 30 publications
4
33
1
1
Order By: Relevance
“…The real US benefit was represented by the six-monthly examination; thus 29.4% of sensitivity was reached, without significant differences amongst the risk groups and age range. Also in this case, our US sensitivity in BRCA1/2 mutated patients (22.7%) compared to results of Van Zelst et al, 28 where total biannual ultrasound sensitivity was 32.1%. Once again, the real added value of US was the six-monthly examination by which 8 patients were found positive (5 aged ≀50 and 3 aged >50 years) with a DR equal to 1.2 × 1,000 person-years, in line with Brem et al that used three-dimensional US to improve the DR of mammographic screening in dense breasts.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The real US benefit was represented by the six-monthly examination; thus 29.4% of sensitivity was reached, without significant differences amongst the risk groups and age range. Also in this case, our US sensitivity in BRCA1/2 mutated patients (22.7%) compared to results of Van Zelst et al, 28 where total biannual ultrasound sensitivity was 32.1%. Once again, the real added value of US was the six-monthly examination by which 8 patients were found positive (5 aged ≀50 and 3 aged >50 years) with a DR equal to 1.2 × 1,000 person-years, in line with Brem et al that used three-dimensional US to improve the DR of mammographic screening in dense breasts.…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, in a previous study the MMG sensitivity increased to 34.6% in patients aged ≀50 years . In another paper, MMG performed on BRCA1/2 carriers showed a 37.2% of sensitivity . Our MMG sensitivity decreased slightly according to age, with a total sensitivity of 55%.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…47 In the study by van Zelst et al, two cancers were in retrospect visible at the 6-month interval, but missed due to their benign appearance. 48 The addition of ultrasound to MRI and mammography leads to a reduction of specificity of between 0% and 5.5%.…”
Section: Ultrasoundmentioning
confidence: 99%
“…20 Conversely to ultrasound and DBT, the additional cancer yield of full diagnostic breast MRI was around 15 per 1000 in women with elevated risk 21 and around 23 per 1000 in an average risk screening setting, 22 with no cancer being detected during the screening interval and a reduction in sensitivity with decreasing biologic aggressiveness. 11,12 The results of breast MRI could not be increased by additional mammography or ultrasound [23][24][25] and a reduction of sequences resulting in an abbreviated breast MRI protocol did not significantly reduce the cancer yield compared with the full diagnostic MRI protocol with an additional cancer yield of 18 per 1000 in women who had already undergone mammography and breast ultrasound. 26 However the application of breast MRI in cancer screening is still impaired: in 2014, the breast cancer consortium reported that of around 25,600 women who met the 20% risk threshold in the U.S. and thereby qualified for breast MRI screening, only 2% had breast MRI performed.…”
mentioning
confidence: 99%